Acetone mobility in zeolite cages with new features in the deuteron NMR spectra and relaxation - E.E. Ylinen; M. Punkkinen; A. Birczyński; Z.T. Lalowicz (Elsevier B.V., 2025)
We studied deuteron NMR spectra and spin−lattice relaxation of deuterated acetone-d6, adsorbed into zeolites NaX (1.3) and NaY(2.4) at 100% coverage of sodium cations. At temperatures roughly below 160 K the deuterons are localized and their NMR characteristics are determined by CD3 rotation and rotational oscillations of acetone molecules. In NaX the CD3 rotation and rotational oscillations about the twofold axis of acetone dominate the spectra below 100 K, while above it oscillations also about other axes become important. In NaY dominant features are related to methyl tunnelling and to a smaller extent to rigid acetones, before the rotational oscillations about twofold axis start to prevail above 40 K. The analysis of the strongly non-exponential magnetization recovery was done by applying the recently introduced method (Ylinen et al., 2015 [12]), improved here to take into account the limited fast recovery at the level crossings, 10% at ωt=ω0 and 28% at ωt=2ω0. At first the experimental recovery is fitted by three exponentials with adjustable weights and decay rates. Then these quantities are calculated from activation energy distributions and known expressions for the deuteron relaxation rate. In NaY two distinctly separate activation energy distributions were needed, the dominant one being very broad. The use of three distributions, two of them covering practically the same energies as the broad one, lead to a somewhat better agreement with experiment. In general the theoretical results agree with experiment within experimental scatter. As the final result the mean activation energies and widths are obtained for activation energy distributions.